Treatment of special products: Implications of the Chair's May 2008 draft modalities text - Bernabe, Riza (International Centre for Trade and Sustainable Development, 2008)
The treatment and selection of special products is a sensitive subject because of the divergent conditions and needs of developing countries. Some countries have negligible tariff bindings while others have high tariff bindings. The results of this study demonstrate that countries with high tariff bindings may rely too heavily on a few commodities to achieve their food security, livelihood and rural development objectives while others with low tariff bindings may face broad economic onsequences that impact those objectives. The case studies conducted highlight the need for some countries to be able to exempt certain products from any cuts. An effective special product designation is an important negotiating objective for many developing countries and this may be contingent upon exemption from cuts for some products.